2023
DOI: 10.1039/d2ta09488f
|View full text |Cite
|
Sign up to set email alerts
|

MXene-decorated flexible Al2O3/TiO2 nanofibrous mats with self-adaptive stress dispersion towards multifunctional desalination

Abstract: Solar-driven interfacial evaporation has shown great promise for desalination due to its high photothermal conversion efficiency. However, for interfacial evaporation, the evaporator must have superior mechanical quality and strong thermal...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Face masks are sanitized to eliminate pathogens using various methods such as dry heat, chemical reagents, nanoparticle implantation, and exposure to steam, supercritical CO 2 , UV, and solar irradiation. While dry heat and steam offer simple sanitization of face masks, the continuous temperature rise can lower filtration performance . Conversely, UV and solar light irradiation effectively neutralize pathogens without compromising FE. , However, high-power UV requires specific chambers, and light irradiation may partially disinfect due to limited penetration. , Chemical sanitization involves agents like detergent, alcohol (IPA and ethanol), H 2 O 2 , hypochlorite, and ethylene oxide, ensuring thorough disinfection . Nevertheless, these harsh chemicals disrupt mask filtration and leave harmful residues that distress the wearer’s skin .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Face masks are sanitized to eliminate pathogens using various methods such as dry heat, chemical reagents, nanoparticle implantation, and exposure to steam, supercritical CO 2 , UV, and solar irradiation. While dry heat and steam offer simple sanitization of face masks, the continuous temperature rise can lower filtration performance . Conversely, UV and solar light irradiation effectively neutralize pathogens without compromising FE. , However, high-power UV requires specific chambers, and light irradiation may partially disinfect due to limited penetration. , Chemical sanitization involves agents like detergent, alcohol (IPA and ethanol), H 2 O 2 , hypochlorite, and ethylene oxide, ensuring thorough disinfection . Nevertheless, these harsh chemicals disrupt mask filtration and leave harmful residues that distress the wearer’s skin .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, UV and solar light irradiation effectively neutralize pathogens without compromising FE. , However, high-power UV requires specific chambers, and light irradiation may partially disinfect due to limited penetration. , Chemical sanitization involves agents like detergent, alcohol (IPA and ethanol), H 2 O 2 , hypochlorite, and ethylene oxide, ensuring thorough disinfection . Nevertheless, these harsh chemicals disrupt mask filtration and leave harmful residues that distress the wearer’s skin . Addressing the need for on-the-spot mask sanitization, antibacterial nanoparticles (Cu, Ag, and TiO 2 ) have been implanted into masks, displaying significant antibacterial properties. , However, these nanoparticles have the potential to detach and be inhaled into the respiratory tract, posing potential health concerns .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of society, the demand for high-performance energy materials is increasing. Owing to the wide application in photoelectrocatalysis, biosensors, supercapacitors, and so on, the preparation of TiO 2 has been a research hot spot for a long time. , Owing to the optical, structured, and electronic advantages, nanostructured TiO 2 -based photoelectrodes are promising for application as photoelectrochemical (PEC) devices, and photoelectrodes based on nanowire, nanorod, and nanoparticle structure have been widely studied. Nowadays, many researchers focus on the catalysts, such as TiO 2 /Ti 3 C 2 , Bi/BiOBr, and N-graphyne/BiOCl 0.5 Br 0.5 , but a few focus on its carrier. However, the photoelectrochemical properties of anodic TiO 2 nanotubes (ATNTs), one of its important carriers, have been studied less. It is worth mentioning that the ATNT array is usually formed in the electrolyte containing halogen ions typically, whereas the dense film in the electrolyte without halogen ions. Some researchers attributed the formation of porous film to an electrochemical dissolution reaction (i.e., TiO 2 + 6F – + 4H + → [TiF 6 ] 2– + 2H 2 O), and some other researchers suggested that the mechanism of porous film formation is related to the contamination layer formed by halogen ions. In summary, all of these studies supported the conclusion that the anion is indispensable for the formation of anodic TiO 2 nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…9 Compared with other seawater desalination technologies, the sustainability and economic advantages of interfacial solar-driven photothermal evaporation make it an attractive solution. 10 Interface solar steam generators capture solar energy and concentrate heat at the gas–liquid interface for efficient water evaporation. To obtain high photothermal conversion efficiency, many researchers have been continuously exploring and developing new photothermal materials.…”
Section: Introductionmentioning
confidence: 99%